The Influence of Job Stress and Workload on Cyberloafing: The Mediating Role of Job Satisfaction - Faishal Farras; Praningrum (Jurnal Manajemen, 2026)
Cyberloafing is behavior exhibited by employees when using office facilities such as the internet for activities unrelated to their work. This can reduce productivity and pose security risks. This study aims to examine how job stress and workload influence cyberloafing behavior, using job satisfaction as a mediator in Bhayangkara Hospital Bengkulu. This study employed a quantitative approach, with data collected via internet-based questionnaires from 115 employees at Bhayangkara Hospital in Bengkulu City. The analysis used Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 3.0. This study reveals that both job stress and workload have a positive and significant influence on cyberloafing behaviour. Meanwhile, job satisfaction has a negative influence on cyberloafing behaviour. The study also found that job stress and workload both positively and significantly influence cyberloafing behaviour. Furthermore, job satisfaction plays a mediating role; lower job satisfaction resulting from high stress and workload contributes to an increase in cyberloafing behavior. This research offers practical implications, particularly in promoting workforce productivity and organizational efficiency. Effective stress and workload management, such as through flexible work policies and employee wellness programs, can increase job satisfaction and reduce non-productive behaviors like cyberloafing. This research aims to provide a reference for future studies while enhancing the concepts or theories that underpin knowledge development in human resource management, specifically on the influence of workload and job stress on cyberloafing behavior.